MEANINGFUL PARTICIPATION DALAM PEMBENTUKAN PERUNDANG-UNDANGAN DAN JAMINAN HAK KONSTITUSIONAL - Elviandri; Muhammad Taufiq; Norrafika Safitri (JOURNAL EQUITABLE, 2024)
The application of the principles and doctrine of meaningful participation is currently considered not to meet the needs of society. This is indicated by the dissatisfaction of several parties who are trying to submit a Judicial Review through a judicial review. The purpose of this article is to find out the application of the principles and concepts of Legislative Formation and meaningful participation in the Formation of Legislation. This research uses a normative juridical research type, with three approaches used, a statutory approach, a conceptual approach and a case approach. The results of this research show that the formation of good laws and regulations must fulfill concepts that are in accordance with the concept of the Pancasila rule of law. The principle of openness is the basis for ensuring legal protection for all levels of society, as well as the community having the opportunity to contribute to the formation of legal regulations. In essence, community participation (meaningful participation) can be understood as input or suggestions for the formation of laws.